Pollution and city size: can cities be too small? - Rainald Borck; Takatoshi Tabuchi (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We study the optimal and equilibrium size of cities in a monocentric city model with environmental pollution. Pollution is related to city size through the effect of population on production, commuting, and housing consumption. If pollution is local, we find that equilibrium cities are too large, mirroring standard results in the theory of city systems. When pollution is global and per capita pollution declines with city size, however, equilibrium cities may be too small.
Keywords: R12; Q54; R13; 330